Sound movement detection deficit due to a brainstem lesion. Issue 5 (May 1997) - Griffiths, T D; Bates, D; Rees, A; Witton, C; Gholkar, A; Green, G G
Abstract : Auditory psychophysical testing was carried out on a patient with a central pontine lesion involving the trapezoid body, who presented with a deficit in sound localisation and sound movement detection. A deficit in the analysis of time and intensity differences between the ears was found, which would explain the deficit in detection of sound movement. The impaired detection of sound movement, due to a lesion interfering with convergence of auditory information at the superior olive, suggests this structure to be critical for human sound movement analysis.